2017
DOI: 10.1111/tpj.13552
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thiamin‐deficient mutant pale green1 lacks thiamin monophosphate phosphatase of the vitamin B1 biosynthesis pathway

Abstract: Thiamin diphosphate (TPP, vitamin B ) is an essential coenzyme present in all organisms. Animals obtain TPP from their diets, but plants synthesize TPPde novo. We isolated and characterized an Arabidopsis pale green1 (pale1) mutant that contained higher concentrations of thiamin monophosphate (TMP) and less thiamin and TPP than the wild type. Supplementation with thiamin, but not the thiazole and pyrimidine precursors, rescued the mutant phenotype, indicating that the pale1 mutant is a thiamin-deficient mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 54 publications
0
68
0
Order By: Relevance
“…., 2015). By contrast, the pale green 1 (pale1) mutant, impaired in the TMP phosphatase, TH2 (At5g32470), is deficient in leaf TDP (Mimura et al, 2016, Hsieh et al, 2017. We examined the B 1 vitamer profile of these lines and could confirm that TDP was increased in THIC THI1 OE but decreased in pale1 ( Figure 3B).…”
Section: Studies In Rat Brain and E Coli Demonstrate That The Tdp VImentioning
confidence: 97%
“…., 2015). By contrast, the pale green 1 (pale1) mutant, impaired in the TMP phosphatase, TH2 (At5g32470), is deficient in leaf TDP (Mimura et al, 2016, Hsieh et al, 2017. We examined the B 1 vitamer profile of these lines and could confirm that TDP was increased in THIC THI1 OE but decreased in pale1 ( Figure 3B).…”
Section: Studies In Rat Brain and E Coli Demonstrate That The Tdp VImentioning
confidence: 97%
“…Phosphorylation of HMP-P to HMP-PP, and subsequently condensation of HMP-PP and HET-P, is done by the action of a bifunctional enzyme, thiamin monophosphate pyrophosphorylase (TH1), which eventually leads to the formation of thiamin monophosphate (TMP) [30,110]. TMP is dephosphorylated to thiamin by a haloacid dehalogenase (HAD) family phosphatase (TH2) [111], and subsequently pyrophosphorylated to thiamin pyrophosphate (TPP) by TPP kinases (TDPKs), which are located in the cytosol (Figure 3) [110,112].…”
Section: Thiamin Biosynthesismentioning
confidence: 99%
“…In addition to its role in central metabolism, studies in different plant species have shown that alterations in the levels of thiamin vitamers result in smaller plants, chlorosis of the leaves, growth retardation, delayed flowering, fitness cost, and an influence on yield penalty [25,26,105,111,133,134]. Some of these phenotypes, such as chlorosis and the delayed flowering, have also been shown to be dependent on the light regime [25,32].…”
Section: The Role Of Thiamin In Mediating Plant Fitness and Acclimationmentioning
confidence: 99%
“…In screens for mutants with altered chloroplast biology at this stage, most studies have identified chloroplast-localized proteins involved in chloroplast development and showing a photosynthesis phenotype. Exceptions include PALE GREEN1 (Hsieh et al, 2017) and SCO3 (Albrecht et al, 2010), which are localized to mitochondria and peroxisomes, respectively. Interestingly, the cytoskeleton is altered in sco3-1, and microtubule inhibitors have similar effects on chloroplast biogenesis to sco3-1 (Albrecht et al, 2010), suggesting a role for the cytoskeleton and peroxisomes in chloroplast biogenesis.…”
Section: Pp7l Contributes To the Tolerance To Abiotic Stressesmentioning
confidence: 99%